Interactions between misonidazole and hyperthermia in EMT6 spheroids. - Morgan, J. E. (Nature Publishing Group, 1981)
The effect of hypoxic misonidazole (MISO) pretreatment on the subsequent heat sensitivity of EMT6 multicellular tumour spheroids has been investigated. Spheroids were grown in static culture and treated when either 200-300 micrometers or 650-800 micrometers in diameter. Pretreatment was carried out in glass spinner vessels containing 100 ml medium with or without 5mM MISO under conditions of hypoxia. Three-hour hypoxic pretreatment with 5mM MISO significantly enhanced the subsequent response of 200 micrometers spheroids to heat at 43 degrees C. Oxic incubation at 37 degrees C between pretreatment and heating caused progressively loss of heat sensitization with time, recovery being almost complete after 6 h. Recovery was inhibited by incubation at 0 degree C during the interval. Preheating 200 micrometers spheroids at 43 degrees C for 2 h increased their subsequent sensitivity to hypoxic MISO at 37 degrees C. These results are discussed in relation to known mechanisms of MISO metabolism.